The Role of Government in the Market for Electric Vehicles : Evidence from China - Li, Shanjun; Zhu, Xianglei; Ma, Yiding; Zhang, Fan; Zhou, Hui (World Bank, Washington, DC, 2020)
To promote the development and diffusion of electric vehicles, central and local governments in many countries have adopted various incentive programs. This study examines the policy and market drivers behind the rapid development of the electric vehicle market in China, by far the largest one in the world. The analysis is based on the most comprehensive data on electric vehicle sales, local and central government incentive programs, and charging stations in 150 cities from 2015 to 2018. The study addresses the potential endogeneity of key variables, such as local policies and charging infrastructure, using the border regression design and instrumental variable method. The analysis shows that central and local subsidies accounted for over half of the electric vehicles sold during the data period. Investment in charging infrastructure is much more cost-effective than consumer purchase subsidies. In addition, the policy that merely provided electric vehicles a distinctively license plate was strikingly effective. These findings demonstrate the varying efficacy across policy instruments and highlight the critical role of government in promoting fuel-saving technologies.